A feasibility study of an advanced skiing simulator - Nemec, B.; Supej, M.; Lahajnar, L. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: This paper describes an advanced skiing Simulator, which is currently in the design phase. The purpose of the Simulator is to simulate, as close as possible, the visual and kinesthetic sensing during alpine skiing.